Hand-Schuller-Christian Disease - Widagdo Widagdo; Rachmad Sadeli; Iskandar Wahidyat (Paediatrica Indonesiana, 1974)
The folllowing case represents a Hand-Schuller-Christian disease as evidenced both by the clinical course and by the examination of biopsy material.